2018
DOI: 10.1136/heartjnl-2018-313463
|View full text |Cite
|
Sign up to set email alerts
|

Association of occupational exposures with cardiovascular disease among US Hispanics/Latinos

Abstract: ObjectiveCardiovascular disease (CVD) is a leading cause of mortality and morbidity in the USA. The role of occupational exposures to chemicals in the development of CVD has rarely been studied even though many agents possess cardiotoxic properties. We therefore evaluated associations of self-reported exposures to organic solvents, metals and pesticides in relation to CVD prevalence among diverse Hispanic/Latino workers.MethodsCross-sectional data from 7404 employed individuals, aged 18–74 years, enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…Other studies are less specific about the particular metals, and point at the possible link based on the exposures in the working environment. For instance, Bulka et al show such association between working with metals and cardiovascular diseases 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies are less specific about the particular metals, and point at the possible link based on the exposures in the working environment. For instance, Bulka et al show such association between working with metals and cardiovascular diseases 35 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, lung complications have been found in hard metalworkers due to cobalt, hexavalent chromium, and nickel exposure [9][10][11], which may be relevant since cobalt, nickel, and chromium (but not hexavalent) are common components in AM powders. Also, lung function and cardiovascular disease (CVD) risk among welders have been extensively studied [12][13][14][15]. Moreover, the risk of negative effects on renal function as result of chromium exposure [16] and hepatotoxic effects as result of chromium exposures have been suggested [17].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies on air pollution and smoking consistently demonstrated cardiovascular injury at levels and durations of exposure much smaller than those associated with lung cancer or even respiratory disease [46]. Furthermore, working exposure was linked to markers of adverse cardiovascular health, such as increased blood pressure, arterial stiffness and decreased heart rate variability [47]. Thus, the co-exposure to fumes/gases in the work environment may enhance the negative effect of air pollution on the risk of CVD acute events.…”
Section: Subanalysesmentioning
confidence: 99%